1991
DOI: 10.2500/105065891782009252
|View full text |Cite
|
Sign up to set email alerts
|

Results of Endoscopic Sinus Surgery for Nasal Polyps

Abstract: Endoscopic sinus surgery (ESS) for nasal polyps was performed on 105 patients, who had a total of 134 operations, on 263 sides. Most patients (84%) had been previously operated on because of recurrent nasal polyps. The subjective results were good in 86% after one or more operations, with a median follow-up of almost 2 years. The objective results, as assessed by nasal endoscopy, show no recurrence in this group in 61%. Preoperative and postoperative lung function was tested in 30 patients with chronic obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Antrochoanal polyps A total of 15 studies were identified that specifically reported on ESS for antrochoanal polyps and their study designs were as follows: 10 case series studies, [96][97][98][99][100][101][102][103][104][105] one case report 106 and four studies of unknown design. [107][108][109][110] Studies were published between 1990 and 2001.…”
Section: Specific Types Of Polypsmentioning
confidence: 99%
“…Antrochoanal polyps A total of 15 studies were identified that specifically reported on ESS for antrochoanal polyps and their study designs were as follows: 10 case series studies, [96][97][98][99][100][101][102][103][104][105] one case report 106 and four studies of unknown design. [107][108][109][110] Studies were published between 1990 and 2001.…”
Section: Specific Types Of Polypsmentioning
confidence: 99%
“…Simple polypectomies were then done when experience showed no correlation between the rate of polyp recurrences and extent of the surgical procedure performed [1]. To date, several series have been published that show good results after endoscopic surgery although with relatively short observation times [12,15,16,20,25,26]. The efficacy of topical steroids in also treating nasal polyps has been highlighted in several studies, both in the prevention of recurrence after polypectomy and in the reduction of polyp size [3,5,10, 11,18,22].…”
mentioning
confidence: 99%
“…Ikeda and colleagues do, however, clearly state that FESS can enhance lung function in those cases where asthma and chronic sinusitis co-exist [13] . In a similar fashion, Vleming's series of 30 cases with both nasal polyps and asthma had improvement in their measures of lung function 64% of the time [30] . Whilst research into the benefit of FESS for asthma does exist, similar research involving subclinical airway flow reduction does not.…”
Section: Discussionmentioning
confidence: 72%